Metacognitive Therapy for Individuals at High Risk of Developing Psychosis: A Pilot Study - Parker, Sophie Kate; Mulligan, Lee D.; Milner, Philip; Bowe, Samantha; Palmier-Claus, Jasper E. (Frontiers in Psychology, 2020)
Developing effective interventions for preventing first episode psychosis have been an important focus of research in the last decade. Psychological treatment in the form of cognitive therapy is currently indicated however, access and resource issues are still a limitation for delivering this within the NHS. Developing treatments which partial out potential active ingredients and are aimed at a range of psychological difficulties seen within this population could lead to more efficacious and efficient treatments. We conducted a single-arm exploratory trial, designed to investigate the feasibility and acceptability of Metacognitive therapy for individuals at ultra-high risk (UHR) of developing psychosis. 10 participants were assessed at baseline, post treatment (12 weeks) and 6 month follow-up with measures of psychotic like experiences, anxiety and depression and metacognitive processes implicated in the model. Retention to treatment was high with 80% treatment adherence gained and an overall average of 8 sessions completed. Clinically significant results were observed in psychotic like experiences, anxiety, depression and functioning with medium to large effect sizes. Measures related to beliefs and processes targeted within MCT showed clinically significant change with medium to large effect sizes. Our results suggest that MCT based upon a specific metacognitive model for individuals meeting ARMS criteria may be an important treatment target and warrants further attention. Limitations are discussed and possible focus for future research. Registration: ISRCTN53190465 http://www.isrctn.com/ISRCTN53190465